Experimental Study on Damage Properties of Granites Under Flowing Acid Solution - Chen, Wei; Wan, Wen; Zhao, Yanlin; Wu, Qiuhong; He, Huan; Peng, Wenqing; Wu, Xiaofan; Zhou, Yu; Wu, Li; Xie, Senlin (Frontiers in Earth Science, 2022)
In order to study the deterioration characteristics of the tunnel surrounding rock under the scouring of flowing groundwater, we ratioed similar acidic solutions based on groundwater composition. The microstructure of granite samples cored on site, deformation features and evolution characteristics of mechanical parameters under saturations with different flow rates and various pH values were analyzed using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), nuclear magnetic resonance (NMR) and X-ray diffraction (XRD). The results indicate that: (1) Compared with the static water condition, the higher flow rate produces greater relative changes in granite’s microstructure, porosity, mass and pH of the immersed solution. Moreover, the rate of change is relatively fast in the early stage, and gradually slows down until it reaches a stable state; (2) Compared with the natural dry condition, the solution with lower pH value causes the structural framework of the specimen to loosen, the mass loss degree to increase and the porosity dispersion to intensify; (3) The dynamic water is more sensitive than the static water to the elastic vertical wave velocity of granite. Compared with the dry sample, the elastic longitudinal wave velocity of the sample in acidic solution with pH = 2 and flow rates of 0, 150 and 300 mm·s-1 for 49 days decreased by 8.7%, 10.9% and 13.5%, respectively, which accelerates the instability and failure of the granite surroundings.